Effect of Chromium on Performance, Antioxidant Status, and Hormonal Parameters of Holstein Calves under Heat Stress - Ahmadikhatir, A; Ghoorchi, T; Toghdory, A; Asadi, M (Journal of the Hellenic Veterinary Medical Society, 2026)
Newborn calf mineral status, including chromium (Cr), is critical for primary growth and reduction of stress effects as well as the health of the newborn calf. Consequently, it is essential to supply minerals at sufficient levels for the suckling calves. In order to evaluate of The effect of feeding milk enriched of inorganic, organic and chromium nanoparticles supplements on performance, blood minerals, biochemical, antioxidant and hormonal of Holstein suckling calves under heat stress, 32 calves with average weight 37± 3 kg in a complete design were randomly selected with 8 replications and 4 treatments. Experimental treatments include milk without chromium supplement (control), milk containing 3 mg of chromium in mineral form per day, milk containing 3 mg of chromium in the form of chromium-methionine per day and milk contained 3 mg of chromium in the form of chromium nanoparticles per day.The results showed that milk enrichment with chromium nanoparticles increased final weight, daily weight gain and dry matter intake. Treatments receiving different forms of chromium showed higher chromium, insulin, glucose, SOD, triiodothyronine, tetraiodothyronine, glutathioneperoxidase and catalase levels in blood than control group. But cortisol, total antioxidant capacity and malondialdehyde of blood in calves consuming different forms of chromium decreased compared to the control group.In general, the use of chromium, especially in the forms of chromium-methionine and chromium nanoparticles, is recommended in calves affected by heat stress.